Increasing Firm Value, Financial Performance Through Sustainable Development Goals Report and GCG in Go Public Companies - Edwin Agus Buniarto; Nordin, Norshahrizan (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This study examines the relationship between the Sustainable Development Goals (SDGs) report, corporate governance, financial performance, and the value of mining companies that go public. The data analysis technique uses Partial Least Square (PLS). The research data is in the form of annual resport, and financial statements of mining companies listed on the IDX from 2019 to 2022. The scope of the study includes various determining factors such as the quality and level of disclosure of the SDG report, the effectiveness of corporate governance mechanisms, and the combined influence of them on financial performance and company value. The findings show that two determining factors significantly affect the value of a company. SDG reports have a significant positive influence on financial performance but a non-significant positive effect on company value. Good Corporate Governance has a significant positive impact on financial performance but has a significant negative effect on the SDG report and company value. Financial performance, in turn, positively and significantly affects the value of a company.